MODELAGEM MATEMÁTICA DE ATUADORES PNEUMÁTICOS COM APLICAÇÃO EM UM SISTEMA MECATRÔNICO - Endler, Luciano; Valdiero, Antonio C.; Andrighetto, Pedro L.; Rafikov, Marat; Ritter, Carla S.; Locateli, Cristiano C.; Zago, Fernando (Salão do Conhecimento, 2013)
Resumo